Varicoceles: Overview of Treatment from a Radiologic and Surgical Perspective - Neves da Silva, Helio V.; Meller, Robert L.; Ogundipe, Eniola A.; Rochon, Paul J. (Seminars in Interventional Radiology, 2022)
A testicular varicocele is the result of the expansion of the venous pampiniform plexus of the scrotum. Often painless, a significant number of patients experience orchialgia, swelling, testicular atrophy, and abnormalities in spermatic parameters. Treatment of symptomatic varicocele involves a radiologic or surgical intervention to obstruct the reflux of venous drainage. Testicular anatomy, diagnostic evaluation and imaging, options for surgical intervention, and a step-by-step description of retrograde embolization and antegrade scrotal sclerotherapy are discussed. Furthermore, included is an overview of postprocedural management and patient outcomes for radiological interventions, and the most up-to-date evidence on the efficacy of varicocele treatments as well as how they compare to each other.
Keywords: varicocele; varicocelectomy; embolization; sclerotherapy; male fertility